2016
DOI: 10.1111/aji.12522
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin‐releasing hormone analogues lead to pro‐inflammatory changes in T lymphocytes

Abstract: GnRH analogues induce pro-inflammatory TH1 shift in T-cell immunity, in vitro. GnRH treatment during assisted reproductive technology cycle might explain a possible cause of inflammatory flare in women with inflammatory conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 47 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…It has already been demonstrated that endotoxin, ischemia reperfusion, atrial natriuretic peptide, BNP, tumor necrosis factor‐alpha, and activated leukocytes, which can induce the expression of heparanases and oxygen radicals, can lead to a destruction of the EGX. In contrast, hydrocortisone seems to prevent damage of the EGX . Shedding of the EGX induces an increase in vascular leakage and thrombocyte adhesion, and damage of the EGX seems to be a key trigger for vascular diseases .…”
Section: Discussionmentioning
confidence: 94%
“…It has already been demonstrated that endotoxin, ischemia reperfusion, atrial natriuretic peptide, BNP, tumor necrosis factor‐alpha, and activated leukocytes, which can induce the expression of heparanases and oxygen radicals, can lead to a destruction of the EGX. In contrast, hydrocortisone seems to prevent damage of the EGX . Shedding of the EGX induces an increase in vascular leakage and thrombocyte adhesion, and damage of the EGX seems to be a key trigger for vascular diseases .…”
Section: Discussionmentioning
confidence: 94%
“…Goserelin triptorelin T cells induce TH1 shift [45] Inhibition of the PI3K-AKT-mTOR pathway PI3K inhibitors pan-PI3K inhibitor macrophages proinflammatory cytokines production and motility↓ [46] Tregs proliferation↓ [47] T cells cytokines and granzyme B secretion↓ [48], tumor infiltration↑ [49] NK and B cells tumor infiltration↑ [49] p110α inhibitor CD8+ T cells tumor infiltration↑ [50], cytokines production and cytotoxicity↑ [51], CD4+ T cells cytokines production↑ [51], Treg polarization↓ [51] MDSCs tumor infiltration↓ [52] p110β inhibitor macrophages phagocytosis↓ [53] neutrophils cell adhesion, spreading and ROS formation↓ [54] p110γ inhibitor myeloid cells tumor infiltration↓ [55] macrophages M1 polarization↑ [56] CD8+T cells PD-1 and CTLA-4 expression↑ [57], tumor infiltra-tion↑ [49] CD4+Tcells, B cells tumor infiltration↑ [49] p110δ inhibitor macrophages tumor infiltration↓ [58] MDSCs, Tregs immunosuppressive function↓ [59] T cells effector response of effector/memory T cells↓ [60] B cells proliferation, survival and differentiation↓ [61] AKT inhibitors capivasertib Tregs proliferation↓ [47] MDSCs differentiation and viability↓ [62] macrophages AKT1 ablation →M1 phenotype, AKT2 ablation →M2 phenotype [63] mTOR inhibitors rapamycin, everolimus mononuclear cells polarization towards M1 macrophage macrophages proinflammatory cytokine production and motility↓ tolerance was revealed to be partially abolished by tamoxifen though suppression of FasL expression as well as blockade of cancer-derived CCL-2/CCL-5 [86,87]. Intriguingly, SERDs (either fulvestrant or JD128), despite lacking a direct antitumor effect on ER-negative BC, were found to reduce the counts of MDSCs and Tregs as well as increase the infiltration of DCs and CD8 + and CD4 + T cells in 4T1 tumor-bearing mice.…”
Section: The Effects Of Serms and Serds On The Tumor Immune Microenvimentioning
confidence: 99%
“…For example, formestane treatment made ER + tumors more sensitive to ADCC by monocytes, suggesting a positive effect of AIs on antigen-specific antitumor immunity [94]. TH1 polarization in the T cell population was also induced by The clinical study (NCT02778685) is recruiting volunteers, with its estimated completion time to be determined GnRHa, increasing the TNFα+/IL-10 + TH cell ratio [45]. In addition, Generali et al and Chan et al evaluated the changes in TIL subtypes in ER + BC patients before and after letrozole/exemestane treatment and found a reduction in Foxp3 + T cells and an increase in CD8 + T cell infiltration among AI responders [41,95].…”
Section: The Effects Of Estrogen Deprivation On the Immune Microenvirmentioning
confidence: 99%
“…Given the increase in cardiac events often within a follow-up of only a year, additional attention has been paid to mechanisms that may induce atherosclerotic plaque destabilization and promote coagulation. For example, a GnRH agonist can increase T cell proliferation resulting in fibrotic cap disruption and plaque instability [61]. A GnRH antagonist will result in a lack of T cell stimulatory response.…”
Section: Atherosclerosis and Plaque Destabilizationmentioning
confidence: 99%